Pemanfaatan Digital Marketing Sebagai Media Pemasaran Dalam Upaya Meningkatkan Kontribusi Ekspor UMKM di Era 4.0 - Lenti Susana Saragih; Aurora Elise Putriku; Silvia Diva Sari; Yessi Novitasari Laia; Yoga Syahputra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the use of digital marketing as a marketing medium in an effort to increase the contribution of the Micro, Small and Medium Enterprises (MSME) sector to national exports in the Industrial Revolution 4.0 era. Digital marketing has opened up new opportunities for MSMEs to reach wider and more diverse markets, beyond traditional geographic boundaries. By using digital platforms, MSMEs can interact with global consumers, introduce their products and services to international markets, and build strong brand awareness. This research uses a literature study method to collect data from various related literature. The research results show that effective use of digital marketing can increase MSME sales turnover and overcome various obstacles faced in implementing digital marketing strategies. Therefore, digital marketing is an important strategy that must be adopted by MSMEs to increase their competitiveness in the global market and achieve sustainable growth.